PEMBUATAN PUPUK ORGANIK UNTUK PERTANIAN BERKELANJUTAN DI DESA SIDOMULYO KECAMATAN PENAWARTAMA KABUPATEN TULANG BAWANG - Theresia Pintaria; Dimas Prasetiyo; reza ramadhan; Ica Pitriani; Nisa Permata Sadila; Muhammad Rhamadani; Wulan Asih Trie Sefiarni (Laporan Upaya Nyata Inovasi Ilmu Komputer, 2024)
Excessive use of chemical fertilizers in agriculture can cause environmental damage and endanger human health. Therefore, education and application of organic fertilizer is needed as a more environmentally friendly and sustainable alternative. This Real Work Lecture (KKN) activity aims to educate the public about the importance of using organic fertilizer and facilitate the manufacture of organic fertilizer independently. This KKN activity was carried out in Sidomulyo Village, Penawar Tama District, Tulang Bawang Regency, Lampung Province. Educational activities are carried out through counseling and training in making organic fertilizer. Extension material includes the benefits of organic fertilizer, types of organic fertilizer, and how to make organic fertilizer. Training in making organic fertilizer is carried out in direct practice using materials that are easily available in the village environment. The results of the activity showed that the level of community knowledge about organic fertilizer increased after attending counseling and training. The community also shows high enthusiasm in making organic fertilizer. It is hoped that this KKN activity can increase public awareness about the importance of using organic fertilizer and encourage the implementation of sustainable agriculture in Sidomulyo Village.